TERMINALIA CHEBULA: SUCCESS FROM BOTANY TO ALLOPATHIC AND AYURVEDIC PHARMACY - Garg, Varun; Kaur, Barinder; Singh, Sachin Kumar; Kumar, Bimlesh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Terminalia chebula (TC) is a unique herb having various therapeutic potentials as anti-inflammatory, antioxidant, anticancer, and digestant. It belongs to family Combretaceae. In the present review, an attempt has been made to decipher classification, chemical constituents, therapeutic uses, and patents that have been reported for TC. Various pharmacological activities of TC that make it as potential medicine and its Ayurvedic formulations are highlighted. Keywords: Terminalia chebula, Anti-oxidant, Anti-cancer, Ayurvedic formulations, Anti-oxidant.